ANALYSIS OF FACTORS INFLUENCING ONLINE CONSUMER BEHAVIOUR - Hovsepyan, N.S. (Modern Psychology, 2020)
The purpose of this article is to discuss what factors influence consumer behavior and the factors, that online customer take into the consideration when purchasing online. For that we analyzed existing literature and went through the online purchasing process and identify the reasons why customers buy online and the barriers for online shopping. After analyzing the literature, we identified that the main factors which consumers take into the consideration are price and convenience. At the same time trust in sellers, and the information they provide, is one of the major issues in the digital environment. Consumers constantly mention the perceived risks associated with using the internet. They believe that there is an additional risk of online fraud and scam.
Keywords: Behavior, person, online shopping, consumer behavior, online shopping influencing factors.